Kekuatan Perbankan Syariah di Masa Krisis - Adib Khusnul Rois; Didik Sugianto (Universitas Muhammadiyah Ponorogo, 2021)
Time keeps turning and times of economic crisis will continue to be repeated with various causes that may be different and require different solutions to problems. In Indonesia, at least three times have experienced crises, namely in 1998, 2008 and most recently in 2020 because of the Covid-19 pandemic. Nobody expects an economic crisis anywhere and anytime. But on the other hand, Islamic banking again proves that the system used is truly resilient to crises, not just a theory and a coincidence because it has been proven three times through the economic crisis and the strength of Islamic banking is very strong to beat conventional banking.